Cladribine Treatment for MS Preserves the Differentiative Capacity of Subsequently Generated Monocytes, Whereas Its Administration In Vitro Acutely Influences Monocyte Differentiation but Not Microglial Activation - Medeiros-Furquim, Tiago; Ayoub, Sinan; Johnson, Laura J.; Aprico, Andrea; Nwoke, Eze; Binder, Michele D.; Kilpatrick, Trevor J. (Frontiers in Immunology, 2022)
Cladribine (2-chlorodeoxyadenosine, 2CdA) is one of the most effective disease-modifying drugs for multiple sclerosis (MS). Cladribine is a synthetic purine nucleoside analog that induces cell death of lymphocytes and oral cladribine treatment leads to a long-lasting disease stabilization, potentially attributable to immune reconstitution. In addition to its effects on lymphocytes, cladribine has been shown to have immunomodulatory effects on innate immune cells, including dendritic cells and monocytes, which could also contribute to its therapeutic efficacy. However, whether cladribine can modulate human macrophage/microglial activation or monocyte differentiation is currently unknown. The aim of this study was to determine the immunomodulatory effects of cladribine upon monocytes, monocyte-derived macrophages (MDMs) and microglia. We analyzed the phenotype and differentiation of monocytes from MS patients receiving their first course of oral cladribine both before and three weeks after the start of treatment. Flow cytometric analysis of monocytes from MS patients undergoing cladribine treatment revealed that the number and composition of CD14/CD16 monocyte subsets remained unchanged after treatment. Furthermore, after differentiation with M-CSF, such MDMs from treated MS patients showed no difference in gene expression of the inflammatory markers compared to baseline. We further investigated the direct effects of cladribine in vitro using human adult primary MDMs and microglia. GM-CSF-derived MDMs were more sensitive to cell death than M-CSF-derived MDMs. In addition, MDMs treated with cladribine showed increased expression of costimulatory molecules CD80 and CD40, as well as expression of anti-inflammatory, pro-trophic genes IL10 and MERTK, depending on the differentiation condition. Cladribine treatment in vitro did not modulate the expression of activation markers in human microglia. Our study shows that cladribine treatment in vitro affects the differentiation of monocytes into macrophages by modulating the expression of activation markers, which might occur similarly in tissue after their infiltration in the CNS during MS.